Comparison of acupuncture and low-level laser for myofascial pain: A pilot study randomized trial (Research, Society and Development, 2025)
Myofascial pain in Temporomandibular Disorder (TMD) involves hypersensitive facial muscle trigger points, affecting quality of life. This trial aimed to evaluate the efficacy of acupuncture and low-level laser therapy for TMD-related pain relief. A randomized controlled trial with 14 participants (10 females, 4 males; mean age 29.5 years) divided into two groups (n=7). Group 1 received ten 20-minute acupuncture sessions every 48 hours, while Group 2 underwent low-power infrared laser therapy (790 nm, 120 mW) on the same schedule. Pain was assessed using a 0–10 Visual Analog Scale (VAS), and neuromuscular activity via bilateral electromyography (EMG) of the temporal and masseter muscles. Statistical analysis used SPSS 22.0 with Wilcoxon and paired t-tests (p